CHAMERION EXTRACT INFLUENCE ON THE HISTOLOGICAL STATUS OF RAT LIVER UNDER ACUTE TOXIC AFFECTION BY TETRACHLORMETANE - Фещенко, Г.І.; Марчишин, С.М.; Volkov, K.S.; Andriyishyn, A.P.; Yarema, N.I. (World of Medicine and Biology, 2019)
In experiments on white rats, the histological structure of the liver was studied under the conditions of acute toxic damage after administration of chameria extract and the Silibinin referential drug. It was revealed that the studied extract has a pronounced protective effect on the liver microstructure. The obtained morphological data showed that chameria extract significantly reduced the damaging effect of carbon tetrachloride and promoted active restoration of the liver parenchyma, had a better positive effect than the Silibinin referential drug. The positive effect of the studied agent is manifested by the activation of regenerative processes, which improves the structural organization of the liver in animals after acute toxic damage with tetrachloromethane.
Keywords: histological examination; liver; experimental toxic hepatitis; carbon tetrachloride; lyophilized chameria herb extract